Parameters of environmental adaptability and stability of parental forms of maize hybrids - G. Ya. Krivosheev; A. S. Ignatiev; A. G. Gorbacheva; I. A. Vetoshkina; N. A. Orlyanskaya; O. N. Panfilova (Зерновое хозяйство России, 2023)
The study of ten parental forms of maize hybrids was carried out in 2017–2019 at five testing establishments with contrasting weather conditions, namely FSBSI Agricultural Research Center “Donskoy”, Rostov Region; FSBSI “All-Russian research institute of maize”, Stavropol Territory; Povolzhsky branch of FSBSI ARRIWG, Volgograd region; FSBSI “All-Russian research institute of maize” (Voronezh branch), Voronezh Region; LLC "Leader", Volgograd region. The purpose of the current study was to estimate the parameters of environmental adaptability and stability, using contrasting moisture points, to evaluate the productive potential of parental forms, i.e. sterile simple maize hybrids to optimize their further use in the breeding and seed production process. The parental forms formed the maximum grain productivity in the Voronezh branch of the All-Russian research institute of maize, where there were formed the most favorable conditions with the environmental index Ij = +2.2; the smallest productivity was formed under the conditions of the ARC “Donskoy” with Ij = –2.3. There have been identified the parental forms (‘Maya M’ and ‘Prestizh M’) with a high potential grain productivity (9.1…9.5 t/ha). There have been identified the parental forms ‘Almaz M’, ‘Avrora S’, ‘Milena M’, ‘Mirt M’, ‘Malvina S’, ‘Raduga S’, ‘Prestizh M’, ‘Maya M’ with high environmental adaptability (bi = 1.03…1.37), high responsiveness to favorable growing conditions. They have been recommended to be used to develop maize hybrids of intensive type. Among them, there have been identified the most adaptable hybrids ‘Mirt M’ and ‘Prestizh M’ with Ymax+Ymin = 6.2…6.8. There have been identified the parental forms ‘Alfa M’ and ‘Istok S’ with low adaptability (bi = 0.76...0.77), but at the same time with high environmental adaptability (σ2d = 0.16...0.20) and high stress resistance (Ymin–Ymax = –3.0…3.1). They have been found preferable for breeding maize hybrids of extensive type for growing under less favorable conditions. The hybrid ‘Istok S’ (Hom = 4) was characterized by the best homeostasis.